(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines the effects of internet retailing in relation to Baramati’s electrical goods. Online retailing has greatly risen in recent years because of digitalization and subsequent covid. Because of its large population, India has a greater than average number of retailers. However, the broad variety of products available on the internet presented a challenge for conventional merchants due to the tempting incentives. The use of electronic products has expanded because of people’s growing technological sophistication. It’s important to concentrate on how digitization will affect existing electronic device stores. This study examines several topics, including the impact of online merchants on traditional stores and what.This paper also covers the impact of digitalization on profitability of traditional retailers.